Effect of adding milk to black tea on vascular function in healthy men and women: a randomised controlled crossover trial - Ahmad, A.; Rich, L.; Koch, H.; Croft, K.; Ferruzzi, M.; Kay, C.; Hodgson, J.; Ward, Natalie (2018)
BACKGROUND: Tea consumption may improve endothelial function and blood pressure via increased bioavailability and bioactivity of nitric oxide. However, questions remain as to the impact of the common practice of adding milk. OBJECTIVE: To investigate the effect of regular consumption of black tea, with and without milk, on vascular function and blood pressure in healthy volunteers. DESIGN: A randomised, controlled, crossover study was performed in 17 healthy volunteers; 7 men and 10 women, mean age 22.4 ± 3.0 years. Participants received each of the following treatments in random order for 4 weeks, with no washout period in between, (i) hot water, (ii) black tea and (iii) black tea with milk. Vascular function was assessed using flow-mediated dilatation (FMD) of the brachial artery at the end of each treatment period. In addition, participants monitored their home blood pressure for the last 7 days of each treatment period. A blood and urine sample was also collected at the end of each treatment period. RESULTS: Black tea increased FMD compared to the hot water control group (1.00 ± 0.18%, P < 0.0001). Black tea with milk decreased FMD compared to both the hot water control (-0.64 ± 0.19%, P = 0.001) and black tea (-1.64 ± 0.19%, P < 0.0001). Compared with hot water, black tea did not alter blood pressure, while black tea with milk increased systolic (1.1 ± 0.5 mmHg, P = 0.03) and diastolic blood pressure (2.0 ± 0.5 mmHg, P < 0.0001). Black tea (-1.8 ± 0.5 bpm, P < 0.001) and black tea with milk (-1.8 ± 0.6 bpm, P < 0.001) lowered heart rate compared to hot water. No significant difference for plasma nitrate or nitrite was observed between treatment groups. CONCLUSIONS: The addition of milk to black tea alters the acute/short-term impact of regular tea consumption on vascular function and blood pressure in young healthy men and women. The exact mechanism for this affect remains unknown and longer-term trials to establish this effect in a range of populations are warranted.